Functional Characterization of VDACs in Grape and Its Putative Role in Response to Pathogen Stress - Xu, Tengfei; Wang, Xiaowei; Ma, Hui; Su, Li; Wang, Wenyuan; Meng, Jiangfei; Xu, Yan (Frontiers in Plant Science, 2021)
Voltage-dependent anion channels (VDACs) are the most abundant proteins in the mitochondrial outer membranes of all eukaryotic cells. They participate in mitochondrial energy metabolism, mitochondria-mediated apoptosis, and cell growth and reproduction. Here, the chromosomal localizations, gene structure, conserved domains, and phylogenetic relationships were analyzed. The amino acid sequences of VDACs were found to be highly conserved. The tissue-specific transcript analysis from transcriptome data and qRT-PCR demonstrated that grapevine VDACs might play an important role in plant growth and development. It was also speculated that VDAC3 might be a regulator of modulated leaf and berry development as the expression patterns during these developmental stages are up-regulated. Further, we screened the role of all grape VDACs’ response to pathogen stress and found that VDAC3 from downy mildew Plasmopara viticola-resistant Chinese wild grapevine species Vitis piasezkii ‘Liuba-8’ had a higher expression than the downy mildew susceptible species V. vinifera cv. ‘Thompson Seedless’ after inoculation with P. viticola. Overexpression of VpVDAC3 resulted in increased resistance to pathogens, which was found to prevent VpVDAC3 protein accumulation through protein post-transcriptional regulation. Taken together, these data indicate that VpVDAC3 plays a role in P. viticola defense and provides the evidence with which to understand the mechanism of grape response to pathogen stress.